CHITINOLYTIC ENZYMES IN THE RUMEN MICROBIAL ECOSYSTEM - J. KOPEČNÝ; Blanka HODROVÁ (Acta Agriculturae Slovenica)
Chitinolytic systems of rumen Clostridia (usually the most active rumen chitinolytic bacteria) and rumen anaerobic fungi were compared in the present study. The chitinolytic enzymes of tested Clostridia strains were represented mainly by extracellular exochitinases, N-acetylglucosaminidases, chitin deacetylases and chitosanases. Zymograms of exochitinases revealed that these enzymes were bound in complexes with MW higher than 100 kDa. Final products of chitin degradation were glucosamine, N-acetylglucosamine and chitin oligosaccharides. Fungal chitinases were represented mainly by extracellular endochitinases and chitin deacetylase in both mono- and polycentric fungi. The main activities in cellular fraction were chitosanase and endochitinase. There were no or low activity of N-acetylglucosaminidase activity in all fungal strains tested. In comparison with rumen chitinolytic bacteria there was lower production of exochitinases and no production of N-acetylglucosaminidase in rumen fungi.